The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.34190/ictr.6.1.1213
|View full text |Cite
|
Sign up to set email alerts
|

Customer Loyalty in Spa Tourism: A Case Study

Abstract: In today's business world, acquiring and retaining customers in the tourism industry is becoming increasingly challenging. High competition, constantly changing markets, and growing customer demands require constant adaptation to new trends and marketing innovations. It is crucial to cultivate customer loyalty, as it leads to repeat business and positive word-of-mouth promotion. Achieving this goal is an increasingly difficult task that requires innovative approaches to service marketing. Tourism includes very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Research has identified various factors that influence customer loyalty in the tourism industry, such as satisfaction, motivation, perceived value, perceived quality, and quality of experience [14]. In addition, factors such as special treatment effect, personal information and experience, and pleasant environment contribute more to loyalty than satisfaction with accommodation or complementary services [15]v. It is crucial for tourism businesses to adapt to new trends and marketing innovations to foster customer loyalty [16].…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified various factors that influence customer loyalty in the tourism industry, such as satisfaction, motivation, perceived value, perceived quality, and quality of experience [14]. In addition, factors such as special treatment effect, personal information and experience, and pleasant environment contribute more to loyalty than satisfaction with accommodation or complementary services [15]v. It is crucial for tourism businesses to adapt to new trends and marketing innovations to foster customer loyalty [16].…”
Section: Introductionmentioning
confidence: 99%